Peranan Majelis Dzikir Dalam Pembentukkan Karakter Remaja - A Maturidi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
This study aims to find out how the role of the Dhikr Council in the formation of adolescent characters carriedout in the Assembly of Dhuafa Tapos Tenjolaya Bogor, Morals or character is human behavior in daily life that hasbeen attached to a person. Morals relating to matters relating to good deeds, bad, right and wrong in the actions ofa human being whose role model is sourced from the Qur'an and the hadith of the Messenger of Allah. In this case,the Dhuafa Assembly as a dzikir council located in Tapos Tenjolaya Bogor has an important role and contribution inthe formation of adolescent character. The writing method used in the study is a qualitative descriptive method. Inthis paper the author discusses the role of the Dhuafa Assembly in the formation of adolescent characters. As for theresults of his research are: 1. The Assembly's aim is to improve the heart (islah al-Qalbi) when his heart is good, hisdeeds will be good 2. The Council of the poor as pioneers in every activity, 3. The Dhuafa Assembly not only conductsdhikr, prayer but also organizes activities to shape the character of adolescents 4. There are factors driving andinhibiting the activities of forming the character of adolescents